Enhancing storage life of onion and garlic - Mahajan, Vijay; Ghodke, Pranjali; Benke, Ashwini; Gupta, A J; Singh, Major (Indian Horticulture, 2019)
Onion and garlic are important spice crop grown all over the world for their special flavour and pungency. However, both are seasonal and semiperishablewhich limits their availability year round. Despite of their ampleproduction, generally 40-50% of the produce failed to reach the market dueto the huge post-harvest losses in storage. Recently more emphasis is givenon awareness for post-harvest technology and its adoption by farmers aswell as traders actively involved in their marketing for its continuous andsteady supply. Therefore, improved technology and storage structures forminimizing these losses have been recommended.